2022
DOI: 10.1111/sdi.13069
|View full text |Cite
|
Sign up to set email alerts
|

The rationale and clinical potential of on‐line hemodiafiltration as renal replacement therapy

Abstract: On‐line hemodiafiltration (ol‐HDF) was developed in the 1980s in response to the unmet medical needs observed with conventional low‐ and high‐flux hemodialysis. Firstly, the limited overall efficacy of conventional HD treatment programs as compared to native kidney function has been consistently documented over the broad MW spectrum of uremic toxins as well as fluid volume and hemodynamic control. Secondly, the unphysiological profile of intermittent treatment leading to repetitive dialysis‐induced hemodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Albumin losses in the dialysate in HF HD were less than 1 g and around 1.5-2.5 g with either HF hemodiafiltration or MCO HD. Likely, the higher removal of albumin does not negatively affect outcomes because trials comparing HD versus HF hemodiafiltration did not demonstrate worst outcomes with latter [57,58].…”
Section: Hd Membranesmentioning
confidence: 98%
“…Albumin losses in the dialysate in HF HD were less than 1 g and around 1.5-2.5 g with either HF hemodiafiltration or MCO HD. Likely, the higher removal of albumin does not negatively affect outcomes because trials comparing HD versus HF hemodiafiltration did not demonstrate worst outcomes with latter [57,58].…”
Section: Hd Membranesmentioning
confidence: 98%
“…The use of on-line hemodiafiltration (OL-HDF) overcomes the technical challenges of bagged replacement dialysate and reduces costs [ 223 ]. Compared with high-flux HD, it can more effectively remove uremic toxins with a broader range of molecular weights [ 224 ] and reduce all-cause and CV mortality, and is associated with a better clinical prognosis [ 225 ]. However, some studies have concluded that this dialysis modality is not significantly different from other modalities [ 226 ].…”
Section: Dialysis Treatmentsmentioning
confidence: 99%
“…Moreover, through the utilization of ultrapure dialysis fluid and a high-flux synthetic membrane, hemodiafiltration (HDF) globally improves the hemocompatibility of the system and reduces inflammation. This method significantly bridges the gap between conventional hemodialysis and native kidney function in clearing larger molecular-weight uremic toxins 3 .…”
Section: Introduction To the Special Issue On Hemodiafiltration In La...mentioning
confidence: 99%